Identification of five new genes on the Y chromosome of Drosophila melanogaster - Carvalho, Antonio Bernardo (The National Academy of Sciences, 2001)
The heterochromatic state of the Drosophila Y chromosome has made the cloning and identification of Y-linked genes a challenging process. Here, we report application of a procedure to identify Y-linked gene fragments from the unmapped residue of the whole genome sequencing effort. Previously identified Y-linked genes appear in sequenced scaffolds as individual exons, apparently because many introns have become heterochromatic, growing to enormous size and becoming virtually unclonable. A TBLASTN search using all known proteins as query sequences, tested against a blastable database of the unmapped fragments, produced a number of matches consistent with this scenario. Reverse transcription–PCR and genetic methods were used to confirm those that are expressed, Y-linked genes. The five genes reported here include three protein phosphatases (Pp1-Y1, Pp1-Y2, and PPr-Y), an occludin-related gene (ORY), and a coiled-coils gene (CCY). This brings the total to nine protein-coding genes identified on the Drosophila Y chromosome. ORY and CCY may correspond, respectively, to the fertility factors ks-1 and ks-2, whereas the three protein phosphatases represent novel genes. There remains a strong functional coherence to male function among the genes on the Drosophila Y chromosome.